Implementation of hyperspectral imaging in a trauma resuscitation room: a randomized controlled trial - Katzenschlager, Stephan; Dietrich, Maximilian; Peterstorfer, Franziska; Manten, Katharina; Forst, Maik von der; Behnisch, Rouven; Leowardi-Bauer, Christine; Studier-Fischer, Alexander; Nickel, Felix; Weigand, Markus A.; Weilbacher, Frank; Popp, Erik (Scandinavian journal of trauma, resuscitation and emergency medicine, 2022)
Hyperspectral imaging (HSI) is a novel imaging technology with the ability to assess microcirculatory impairment. We aimed to assess feasibility of performing HSI, a noninvasive, contactless method to assess microcirculatory alterations, during trauma resuscitation care.